Unravelling the relationship between functional capacity and physical activity in people with interstitial lung disease - Grave, A. S. (2022)
Functional capacity (FC) and functional performance are distinct domains of functional status. Low functional capacity (FC) is com-monly reported in people with interstitial lung disease (ILD). How-ever, the literature on functional performance - possible to be ob-jectively measured quantifying the physical activity (PA) levels - and on the relationship between FC and PA of this population is still scarce. Thus, this study aimed to: i) characterise the PA levels; ii) explore the relationship between FC and PA; and, iii) determine the distribution across the four quadrants of FC and PA of people with ILD. A retrospective cross-sectional study was conducted. PA levels were assessed with accelerometry (Actigraph® GT3X+), through steps/day and time spent in moderate-to-vigorous (MVPA) PA. Par-ticipants wore the Actigraph® for, at least, 4 consecutive days (7:00am-10:00pm). FC was assessed with the number of repetitions performed in the 1-minute-sit-to-stand (1-minSTS). PA levels were compared between three ILD diagnostic categories (i.e., fibrotic Hypersensitivity Pneumonitis [fHP], Idiopathic Pulmonary Fibrosis [IPF] and Connective Tissue Disease-related ILD [CTD-ILD]) and se-verity, using the ILD-GAP Index model (0-3, ≥ 4). U Mann-Whitney and Kruskal-Wallis tests were used to compare groups. Spearman’s Correlation was used to analyse the correlation between FC and PA. For the quadrants analysis, participants were divided into the fol-lowing: 1) low FC (1-minSTS < 70% predicted) and low PA (< 5,000 steps/day or < 150 min/week of MVPA) – “can’t do, don’t do”; 2) preserved FC (1-minSTS ≥ 70%), low PA (< 5,000 steps/day/< 150 min/week of MVPA) – “can do, don’t do”; 3) low FC (1-minSTS < 70% predicted), preserved PA (≥ 5,000 steps/day/ ≥ 150 min/week of MVPA) – “can’t do, do do”; 4) preserved FC (1-minSTS ≥ 70%), pre-served PA (≥ 5,000 steps/day/ ≥ 150 min/week of MVPA) – “can do, do do”. Forty-nine volunteers were included (68 [63-76] years; 23 [46.9%] male, FVC 84 [69-95]% predicted; DLCO 57 [40-73]% pre-dicted). PA levels ranged between 792-113,670 steps/day and 2-1,604 min. spent in MVPA. PA levels across ILD subtype were not different (p = 0.061-0.609) however, significant differences were found across disease severity (GAP0-3 = 41 GAP ≥ 4 = 8 steps/day p = 0.003, GAP0-3 = 41 GAP ≥ 4 = 8 MVPA p = 0.015). Significant, mod-erate and positive correlations were found between FC and PA for both, steps/day (rs = 0.53, p < 0.001) and MVPA (rs = 0.40, p = 0.005). Participants’ distribution on the FC and PA (steps/day) quad-rants was: 22 (45%) “can’t do, don’t do”; 7 (14%) “can do, don’t do”; 7 (14%) “can’t do, do do”; 13 (27%) “can do, do do”. Partici-pants’ distribution between FC and PA (MVPA) quadrants was: 20 (41%) “can’t do, don’t do”; 5 (10%) “can do, don’t do”; 9 (18%) “can’t do, do do”; 15 (31%) “can do, do do”. People with ILD tend to be physically inactive. PA levels decrease with ILD severity and there is a relationship between FC and PA in this population. Ap-plicability of the FC-PA quadrant may guide personalised interven-tions to optimise outcomes of these meaningful domains in ILD.